Fast prototyping microfluidics: Integrating droplet digital lamp for absolute quantification of cancer biomarkers - Oliveira, Beatriz (2020)
UID/CTM/50025/2019 UID/Multi/04378/2019 Inn-INDIGO/0002/2015 PTDC/BTM-SAL/31201/2017 SFRH/BPD/124311/2016